The Vascular Flora of the Railway Grounds of the Pabianice Town - Warcholińska, Aurelia Urszula; Suwara-Szmigielska, Sylwia (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2009)
In the paper a list and general characterization of vascular plants recorded on railway grounds of the town of Pabianice is presented. The great diversity o f habitats within the railway grounds as well as their inclination to be colonized by numerous introduced species resulted in high variety of vascular plants there. This flora consists of 382 taxa.